Ministry of Petroleum and Mineral Resources Decree No. 581 and 582 of the year 2022 = وزارة البترول والثروة المعدينة قرار رقم 581 و 582 لسنة 2022 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic